2018
DOI: 10.1111/ajt.14567
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CD47 monoclonal antibody therapy reduces ischemia-reperfusion injury of renal allografts in a porcine model of donation after cardiac death

Abstract: We investigated whether blockade of the CD47 signaling pathway could reduce ischemia-reperfusion injury (IRI) of renal allografts donated after cardiac death (DCD) in a porcine animal model of transplantation. Renal allografts were subjected to 30 minutes of warm ischemia, 3.5 hours of cold ischemia, and then perfused with a humanized anti-CD47 monoclonal antibody (CD47mAb) in the treatment group or HTK solution in the control group (n = 4/group). The animals were euthanized five days after transplantation. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 47 publications
(93 reference statements)
1
26
0
Order By: Relevance
“…Interestingly, with the exception of IL-6, there was no reduction in the mRNA expression of TNF-α, IL-1β, CCL2, or CXCL2 in the αCD47Ab-treated mice. A lack of impact on TNF-α mRNA expression in response to CD47 blockade has also been noted elsewhere, indicating this pathway is not directly involved in CD47-mediated cellular injury during IRI 21,48 . The primary focus of this paper was the acute phase of injury secondary to IRI, which manifests as delayed graft function (DGF) in the kidney transplant recipient.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Interestingly, with the exception of IL-6, there was no reduction in the mRNA expression of TNF-α, IL-1β, CCL2, or CXCL2 in the αCD47Ab-treated mice. A lack of impact on TNF-α mRNA expression in response to CD47 blockade has also been noted elsewhere, indicating this pathway is not directly involved in CD47-mediated cellular injury during IRI 21,48 . The primary focus of this paper was the acute phase of injury secondary to IRI, which manifests as delayed graft function (DGF) in the kidney transplant recipient.…”
Section: Discussionsupporting
confidence: 56%
“…There was no immunofluorescence evidence that this cold perfusion component of the αCD47Ab dose caused effective binding to its receptor. In contrast, Xu et al showed renal binding after pre-implantation delivery of αCD47Ab to porcine kidneys via a direct renal artery cold flush 48 . However, these authors used a dose that was approximately 50 times greater than that used in this study.…”
Section: Discussionmentioning
confidence: 91%
“…Anti-CD47 antibodies and small molecules that mimic the TSP binding site for bFGF are being tested in clinical trials, in preclinical models, or are under development for various diseases. 169,[178][179][180][181][182] Antagonists of these antiangiogenic TSP1 functions have not been tested with antagonists of TSP1's TGF-β activating function. Combined use of a variety of TSP1 functional antagonists could represent a multipronged approach to treating the complex pathogenesis of fibrosis.…”
Section: Tsp1 As a Therapeutic Targetmentioning
confidence: 99%
“…20,21 Briefly, the donors and recipients were intramuscularly injected with the analgesic of buprenorphine 0.005-0.1 mg/ kg, and anesthesia was induced with a TKX cocktail (Telazol 4 mg/ kg, ketamine 2 mg/kg, and xylazine 2 mg/kg), and maintained with 2.5%-4% isoflurane in oxygen at a flow of 2.0 L/minute. 20,21 Briefly, the donors and recipients were intramuscularly injected with the analgesic of buprenorphine 0.005-0.1 mg/ kg, and anesthesia was induced with a TKX cocktail (Telazol 4 mg/ kg, ketamine 2 mg/kg, and xylazine 2 mg/kg), and maintained with 2.5%-4% isoflurane in oxygen at a flow of 2.0 L/minute.…”
Section: Porcine Kidney Transplantation and Experimental Designmentioning
confidence: 99%
“…Animals were anesthetized and transplanted as previously described. 20,21 Briefly, the donors and recipients were intramuscularly injected with the analgesic of buprenorphine 0.005-0.1 mg/ kg, and anesthesia was induced with a TKX cocktail (Telazol 4 mg/ kg, ketamine 2 mg/kg, and xylazine 2 mg/kg), and maintained with 2.5%-4% isoflurane in oxygen at a flow of 2.0 L/minute. An abdominal midline approach was used to expose the kidneys and vasculature.…”
Section: Porcine Kidney Transplantation and Experimental Designmentioning
confidence: 99%